ANALYSIS OF MORAL VALUES IN MALIN KUNDANG FOLKLORE AND ITS UTILIZATION AS TEACHING MATERIAL FOR STORY TEXTS IN SENIOR HIGH SCHOOL - Mar'atun sholikhah; Dede Endang Mascita; Nuning Wahyuningsih (Cirebon International Conference on Education and Economics Proceeding, 2024)
This research aims to analyze the moral values contained in the Malin Kundang folklore and to develop Indonesian language learning materials for class both verbally and written. 4.7 Retell the contents of folk tales heard or read. The research method used is a qualitative descriptive method which describes phenomena with words and quotations. The data source comes from the folklore book Malin Kundang by Yuliadi Soekardi and Usyahbudin. The results of the research reveal various moral values contained in Malin Kundang's folklore books. These moral values contain four aspects of human relationships in morals, namely: 1) moral values of human relationships with themselves, 2) moral values of human relationships with other humans, 3) moral values of human relationships with God, and 4) moral values moral relationship between humans and nature. The conclusion of this research shows that most of the folklore text titles in the book have three aspects of moral values: human relationships with themselves, human relationships with other humans, and human relationships with God, moral values in folklore Malin Kundang contains moral values that can be applied in everyday life. Apart from that, this research produced a design of teaching materials for learning folklore texts for class.